Generation of an induced pluripotent stem cell line (DHMCi006-A) from a patient with autosomal recessive polycystic kidney disease (ARPKD) carrying a compound heterozygous missense mutation in the fibrocystin encoding PKHD1 gene - Fluhr, Theresa; Tabatabaeifar, Mansoureh; Syring, Hanna; Göhring, Gudrun; Schaefer, Franz; Jung-Klawitter, Sabine (Stem cell research, 2021)
Mutations in the PKHD1 gene, encoding for the ciliary protein fibrocystin, play a major role in the cystogenesis in autosomal recessive polycystic kidney disease (ARPKD), a severe pediatric kidney disorder. Peripheral blood mononuclear cells (PBMCs) from a female patient carrying a compound heterozygous PKHD1 mutation (c.6331A>G(;)7717C>T) were obtained and reprogrammed by viral transduction using the Cytotune®-iPS 2.0 Sendai Reprogramming Kit (Invitrogen). The resulting iPSCs display a normal karyotype, express pluripotency markers, and show the potential for spontaneous differentiation in vitro, offering a useful tool for studying ARPKD pathomechanisms and drug screening.
Gesehen am 02.12.2021